THE JURIDICAL BASIS OF GOVERNMENT REGULATION NUMBER 3 YEAR 2014 ON ACCELARATION DEVELOPMENT OF DISVANTAGED REGIONS REVIEW FROM THE PERSPECTIVE OF VALIDITY THEORY (Geltung) - Jenar , Saptono; Harvelian, Agnes (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2021)
Research of validity (geltung) is discussing about how a rule applied in the administration of the state and government. This research intends to examine the enactment of Government Regulations on the acceleration of development of disadvantaged regions based on legal theory. This is a normative research, using literature studies, with the statutes approach and conceptual approach, and using descriptive analysis. Through this research, it was found that government policies related to the implementation of acceleration for development of disadvantaged regions has no legal basis for its validity, and it has been put aside of the higher legal norms (hierachichal of regulations) especially Laws Number 39 year 2008. Therefore, it is recommended that every policy implementation at the level of Government Regulation must be ordered by the rigt of higher Regulations or based on concretely regulated authority by higher norms.